2016
DOI: 10.1016/j.ajpath.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Biomarkers of Acute Muscle Damage in Rats

Abstract: Skeletal muscle damage is an often-occurring event. Diagnosis using the classic blood marker creatine kinase sometimes yields unsatisfactory results due to great interindividual variability. Therefore, the identification of reliable biomarkers is important. Our aim was to detect and characterize circulating miRNAs in plasma in response to acute notexin-induced muscle damage in rats. Real-time quantitative RT-PCR profiling led to the identification of miRNAs that were highly increased in plasma in response to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 58 publications
5
58
1
Order By: Relevance
“…To investigate the effect of an acute muscle injury in the absence of contraction on c‐miRNA levels, we studied plasma miRNA profiles in rats after an intramuscular injection of notexin, a myotoxin known to provoke massive myofibre necrosis. We found a substantial increase in circulating myomiRs that could efficiently discriminate between damaged and non‐damaged animals . Concomitant myofibre necrosis and a reduction in myomiRs within damaged muscle tissue suggest that a passive release by injured myofibres may account for high circulating levels.…”
Section: Circulating Myomirs and Muscle Damagementioning
confidence: 73%
“…To investigate the effect of an acute muscle injury in the absence of contraction on c‐miRNA levels, we studied plasma miRNA profiles in rats after an intramuscular injection of notexin, a myotoxin known to provoke massive myofibre necrosis. We found a substantial increase in circulating myomiRs that could efficiently discriminate between damaged and non‐damaged animals . Concomitant myofibre necrosis and a reduction in myomiRs within damaged muscle tissue suggest that a passive release by injured myofibres may account for high circulating levels.…”
Section: Circulating Myomirs and Muscle Damagementioning
confidence: 73%
“…Pick-&-Mix microRNA PCR panels (Exiqon) were used [1], 500 µL 2× PCR Master mix were combined with 6.25 µL cDNA and 493.75 µL sterile water. Then, 10 µL were distributed in each well.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Then, a set of miRNAs was selected based on detectability and alteration in response to injury, and was measured on individual samples. Muscle-specific miRNAs results have been described elsewhere [1]. Fig.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, interference of the exosome biosynthesis process or disruption of exosomal membranes reduces extracellular miRNA content [59]. Most recently, it has been shown that serum miRNAs can be found in both vesicular and non-vesicular fractions in response to tissue damage in rats [95]. Although the manner in which miRNAs are transported in the circulation may be condition dependent, they appear to be abundantly expressed and likely exert effects in different tissue types.…”
Section: Circulating Mirnasmentioning
confidence: 99%